2013
DOI: 10.1155/2013/127017
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeaeInduces a Tolerogenic Phenotype in Macrophages to Modulate Host Immunity

Abstract: Neisseria gonorrhoeae is the etiological agent of gonorrhoea, which is a sexually transmitted disease widespread throughout the world. N. gonorrhoeae does not improve immune response in patients with reinfection, suggesting that gonococcus displays several mechanisms to evade immune response and survive in the host. N. gonorrhoeae is able to suppress the protective immune response at different levels, such as B and T lymphocytes and dendritic cells. In this study, we determined whether N. gonorrhoeae directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…8), we postulate that M2 macrophages may be the more relevant phenotype within the genital tract. Escobar et al (2013) had previously suggested that cytokines induced by N. gonorrhoeae from RAW 264.7 mouse macrophages correspond to an M2 profile and had recently published that N. gonorrhoeae can polarize Survival, apoptosis and cytokine modulation by Neisseria gonorrhoeae in human macrophages 555 human macrophages to an M2 profile (Ortiz et al, 2015). The phenotype of macrophages in the genital tract of patients will have to be investigated to determine whether there is polarization during natural gonococcal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8), we postulate that M2 macrophages may be the more relevant phenotype within the genital tract. Escobar et al (2013) had previously suggested that cytokines induced by N. gonorrhoeae from RAW 264.7 mouse macrophages correspond to an M2 profile and had recently published that N. gonorrhoeae can polarize Survival, apoptosis and cytokine modulation by Neisseria gonorrhoeae in human macrophages 555 human macrophages to an M2 profile (Ortiz et al, 2015). The phenotype of macrophages in the genital tract of patients will have to be investigated to determine whether there is polarization during natural gonococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of TNF-α and GM-CSF can also contribute to prolong the life of PMNs. The secretion of the regulatory cytokine IL-10 can have a potent T-cell suppressive function (Escobar et al, 2013), and it has been previously shown that N. gonorrhoeae suppresses T-cell function (Boulton and Gray-Owen, 2002;Lee et al, 2008;Zhu et al, 2012) and may induce a localized immune suppression (Liu et al, 2014). IL-6 and TNF-α may also trigger the influx of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…gonorrhoeae potently inhibits the ability of antigen-primed bone-marrow-derived DCs (BMDC) to trigger T-cell proliferation by inducing expression of both immunosuppressive cytokines and tolerance-inducing cell surface protein [ 14 ]. Furthermore Escobar et al [ 15 ] recently demonstrated that GC modulates MΦ and their functionality, producing a shift towards anti-inflammatory cytokine production, inefficient upregulation in molecules involved in antigen presentation and T-cell activation and a poor allogeneic T-cell stimulatory activity [ 15 ]. These studies showed that N .…”
Section: Introductionmentioning
confidence: 99%
“…Although N . gonorrhoeae has been reported to modulate MΦ [ 15 , 23 ], GC influence on MΦ polarization has not been yet explored. In order to address this issue we studied the effect of N .…”
Section: Introductionmentioning
confidence: 99%
“…The first of these, is the recent findings that N. gonorrhoeae proactively manipulates the host immune response for its own benefit, by selectively eliciting innate host defenses that it can survive while concomitantly suppressing adaptive immune responses that would eliminate it [11]. Several mechanisms have been described that contribute to this ability, including inactivation of T-helper cells [12], modulation of dendritic cells or macrophages [13,14] and upregulation of IL-10, TGF-β and type 1 regulatory T cells [15]. These findings reveal new understandings of immunity to N. gonorrhoeae and suggest that novel approaches to reverse gonococcus-induced immunosuppression might be fruitful; moreover they inform new strategies for vaccine development.…”
Section: Editorial Russellmentioning
confidence: 99%